PENENTUAN KRITERIA DAN SUB-KRITERIA PEMILIHAN PROYEK BERDASARKAN TAHAP PELAKSANAANKERJASAMA PEMERINTAH DENGAN BADAN USAHA DI BIDANG PERKERETAAPIAN INDONESIA - Herman, Herman; Santosa, Wimpy; Sjafrudin, Ade (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Public Private Partnership for railway transportation had been arranged in The Law No. 23/2007. Selection of railway operations to be offered to the private sector through Public Private Partnership scheme takes a set of criteria so that the project could benefit the government and private parties. This implementation had been arranged in The State Ministry for Development Planning/Head of National Development Planning Agency No. 3/2012, the General Guide of Implementation of Government Cooperation with Enterprises in Infrastructure Provision. Of the partnership split up into Palnning of Cooperation Project, Completion of Cooperation Project, Transaction of Cooperation Project and Implementation Management of Cooperation Agreement. This study aims to get the criteria of project selection in railway transportation for each level of the implementation of cooperation between public and private. This research the collecting of data has been conducted by interview. The numbers of respondents who are interviewed are 13 respondents. Statistical analysis determination of group of criteria and sub-criteria to Must Criteria and Want Criteria used Sign Test. The conclusion of the study is Planning of Cooperation Project consists of 2 Must Criteria (4 sub-criteria) and 2 Want Criteria (6 sub-criteria), Completion of Cooperation Project consists of 5 Must Criteria (12 sub-criteria) and 2 Want Criteria (6 sub-criteria), and Transaction of Cooperation Project consists of 5 Want Criteria (13 sub-criteria ) and 3 Want Criteria ( 9 sub-criteria ).